Effect of the Student Teams Achievement Division Learning Model Assisted by Quizizz on Students Learning Motivation in the Subject of History of Islamic Culture - Sari, Fintia Monica; Yusnita, Erni; Ali, Syamsuri; Baharudin, Baharudin (Sekolah Tinggi Agama Islam Sumatera Medan, 2025)
This study aims to determine the effect of the Student Teams Achievement Divisions learning model assisted by Quizizz on the motivation of Islamic Religious Education students in SKI subjects at MTs Ismaria Alquraniyyah Bandar Lampung. This study uses a quantitative approach, quasi-experimental design. Class VII C was used as the experimental class and class VII B as the control class. The final test was in the form of a post-test using a non-test instrument (questionnaire). The tests used were instrument tests (validity and reliability), prerequisite tests (normality and homogeneity), and hypothesis tests (independent sample t-test). Based on the research results, a reliability value of 0.900 > 0.6 was obtained. Then, in testing the Independent Sample T-Test hypothesis, a sig. value of 0.871 > 0.005 was obtained, so Ha was rejected. This does not indicate any effect on student learning motivation between classes that use the Student Teams Achievement Divisions learning model assisted by Quizizz and classes that use conventional learning. The implication of this study is that it is important to find solutions through the use of more interesting and interactive media and models. This study proposes a different approach by combining the Quizizz-based Student Teams Achievement Divisions learning model. This study focuses on the aspect of learning motivation in Islamic Cultural History.